Rancang Bangun Media Pengenalan Jenis Alat/Pil Kontrasepsi Untuk Keluarga Berencana Pada Kampung KB Berbasis Web: Rancang Bangun Media Pengenalan Jenis Alat/Pil Kontrasepsi Untuk Keluarga Berencana Pada Kampung KB Berbasis Web - Salamudin, Salamudin; Suzana, Middia (Universitas Lembah Dempo, 2021)
Kampung KB was launched by Mr President of the Republic of Indonesia (Ir. Joko Widodo) in January 2016 which aims to improve the quality of life of people at the village level or equivalent through the Family Planning and Family Development Population (KKBPK) program as well as other related sector developments to realize quality small families. Meanwhile, kampung KB was formed in addition to increasing the participation of government, non-government and private institutions in facilitating, assisting and fostering the community to organize KKBPK programs and related sector development. Kb program is carried out with the use of various types of contraceptives for Couples of Childbearing Age (PUS). The government is now actively promoting the KB program with the target of Child-Bearing Age Couples (PUS) at the age of 15-49 years. Kb communication, information and education (KIE) activities in Indonesia are lighting and socialization activities of kb programs through various media. The media has an important role in socializing family planning. One of them is through the media website. The purpose of this research is to produce web-based media that can introduce the types of contraceptive devices/pills that can be accessed by acceptors and become a medium of socialization of family planning field officers (PLKB) in the village of KB. The method of data collection is done by direct observation, literature review and observation method. Designing the needs of this website will use Unified Modeling Language and implemented with the CodeIgniter framework.